Horticulture for a greener world - Hubbard, L. Ron (La Fayette Ron) 1911-1986.; Church of Scientology (St. Hill, West Sussex, England).; L. Ron Hubbard Library; Bridge Publications (Commerce, California Bridge Publications, 2012)
"In this very special story of transcendent revelations and global repercussions, track the course of L. Ron Hubbard's horticultural discoveries. Told through articles and personal notes--here is a journey of discovery bearing upon all living things and the very essence of life itself."-- Source other than Library of Congress.
An introduction to L. Ron Hubbard -- Experimental background -- Duties of a grounds manager -- Experimental procedure -- Grow lights -- The magic of seed irradiation -- Light and your plants -- Automating your greenhouse -- Sowing and soil -- On germination rates -- The first crop of 1960 -- Advice and diagnosis -- Methods of transplanting -- Advanced experimentation -- The inner life of plants revealed -- Revolution rocks the plant kingdom! -- An insider's view -- Corollary discoveries -- Cultural outgrowth.
Keywords: Hubbard, L. Ron -- 1911-1986 -- Philosophy; Horticulture -- Experiments; Horticulture -- Research; Plants -- Experiments